Herb Drug Pharmacokinetic Interaction of 5 Fluorouracil (5-FU) with Turmacin in Albino Rats - Trilochan Satapathy; Rajni Yadav; Amit Roy (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Cancer is the leading cause of death worldwide. 5 Fluorouracil (5FU) is commonly used anticancer drug for treatment of breast and colon cancer according to the survey conducted in one of the cancer research hospital of the state. Patient tends to use herbal alternative medicines as supportive and palliative care in cancer treatment, one such herb intake reported was turmeric. We selected the novel solvent free phytochemical from turmeric (Curcuma longa) named turmacin to study its pharmacokinetic drug interaction with 5 Fluorouracil (5 FU). Method: To study the pharmacokinetic herb-drug interaction of turmacin with 5 FU healthy albino rats were used and their blood samples were analyzed using high performance liquid chromatography (HPLC), to record the levels of both drugs in rat blood. Rats were divided into three groups, one group was administered 5 FU(20mg/kg, ip) alone, while the other two were treated with dose of turmacin (100 mg/kg/day) for 7 consecutive days in combination with 5 FU with last group. Results: The results clearly showed that 5 FU blood levels showed slight variation in terms of increased volume of distribution withdose of turmacin (100mg/kg/day). However no significant changes were observed in blood levels with dose of turmacin (100mg/kg/day). The mean residence time was also increased in the samples of 5 FU along with high dose of turmacin (100mg/kg/day). Conclusions: Overall pharmacokinetic study confirms the safety of turmacin with 5 FU only at low dose and high doses should not be used for safety concern of patients.